2015
DOI: 10.1021/jacs.5b07998
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Hydroamination Gold Catalyst by Oxidation of a Redox-Noninnocent Chlorostibine Z-Ligand

Abstract: In search of new platforms that support redox-controlled catalysis, we have investigated the noninnocent behavior of chlorostibine ligands coordinated to gold. The gold chlorostibine complex ((o-(Ph2P)C6H4)2SbCl)AuCl (1-Cl) undergoes a clean oxidation reaction on treatment with PhICl2. This oxidation reaction affords the corresponding trichlorostiborane complex ((o-(Ph2P)C6H4)2SbCl3)AuCl (2-Cl), which can be converted into the more tractable trifluoride analogue ((o-(Ph2P)C6H4)2SbF3)AuCl (3-Cl) by treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
87
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(91 citation statements)
references
References 72 publications
3
87
0
Order By: Relevance
“…[1] Antimony derivatives,b ecause of their intrinsically higher Lewis acidity, [2] are also drawing considerable attention both in the areas of small-molecule activation and catalysis, [3] as well as in anion complexation. [7] Based on the same principle,w ea lso found that antimony(III) halides could serve to promote the activation of transition metals either by direct interaction with the metal (III) [8] or anion abstraction (IV) [9] (Figure 1). [7] Based on the same principle,w ea lso found that antimony(III) halides could serve to promote the activation of transition metals either by direct interaction with the metal (III) [8] or anion abstraction (IV) [9] (Figure 1).…”
mentioning
confidence: 97%
“…[1] Antimony derivatives,b ecause of their intrinsically higher Lewis acidity, [2] are also drawing considerable attention both in the areas of small-molecule activation and catalysis, [3] as well as in anion complexation. [7] Based on the same principle,w ea lso found that antimony(III) halides could serve to promote the activation of transition metals either by direct interaction with the metal (III) [8] or anion abstraction (IV) [9] (Figure 1). [7] Based on the same principle,w ea lso found that antimony(III) halides could serve to promote the activation of transition metals either by direct interaction with the metal (III) [8] or anion abstraction (IV) [9] (Figure 1).…”
mentioning
confidence: 97%
“…[1] In particular,cooperation between an electronrich metal and s-acceptor ligand ("Z-type ligand") has recently become of increasing interest. [14,15] Whereas the chemistry of complexes containing group-15-based Lewis acids has recently received increased attention, [16][17][18] most examples of such cooperative reactivity and coordinative flexiblity have exploited boranes (BR 3 )a st he Z-type ligand. [14,15] Whereas the chemistry of complexes containing group-15-based Lewis acids has recently received increased attention, [16][17][18] most examples of such cooperative reactivity and coordinative flexiblity have exploited boranes (BR 3 )a st he Z-type ligand.…”
mentioning
confidence: 99%
“…Taking this interaction into account, the antimony center adopts a disphenoid geometry, as indicated by the Au(1)‐Sb(1)‐C(7) and Au(2)‐Sb(2)‐C(37) angles of 171.4(2)° and 169.9(2)°, and C(1)‐Sb‐C(13) and C(31)‐Sb(2)‐C(43) angles of 95.5(3)° and 96.4(3)°. Similar geometries have been observed at the antimony centers in the related tris‐ and bis‐phosphinylstibine gold complexes . As in 1 , these metrical parameters show that the antimony atom does not interact strongly with the gold center as a Lewis base .…”
Section: Resultsmentioning
confidence: 99%
“…A related strategy involves the design of ligands containing pendent Lewis acid functionalities, which are able to effect intramolecular halide abstraction from the gold center as in the case of C . In addition to facilitating halide abstraction, pendent Lewis acids have also been shown to improve the activity of electrophilic catalysts, even in cases when the structurally observed M→LA appears to be weak . Finally, we note that the zwitterionic products of Lewis acid‐mediated intramolecular halide abstraction bear comparison to a number of zwitterionic gold complexes featuring an anionic N ‐heterocyclic carbene (NHC) coordinated to a cationic gold center, a number of which have been shown to be active electrophilic catalysts…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation